Karakterisasi Mesin Perajang Porang (Amorphophallus meullleri) Berdasarkan Variasi Kecepatan Putaran Mesin dan Karakteristik Fisik Chip Porang - Amrullah, Shafwan; Oktaviananda, Cyrilla; Asruldin, Asruldin (Agriculture Faculty, 2023)
Porang tubers or in Latin Amorphallus meulleri is a type of tuber plant that is currently getting special attention from the world. Indonesia is one of the largest suppliers. The benefits of porang tubers, apart from being a supplier of starch, are also a source of medicine. Porang tubers are currently an Indonesian export commodity, but in the form of chips. The existence of this condition certainly forces these exporters to innovate to develop porang products in the form of chips. Therefore, in this study, the design and manufacture of a porang chopper machine into chips was carried out. The research continued by testing the characteristics of the machine by testing variations in engine speed (600, 700, and 800 rpm) on engine performance (cutting capacity, average thickness, percentage of damage, percentage of material left behind, and energy, and cost), one of which was marked with the machine's success in creating perfect porang chips based on export standards. The results of this study show the best average cutting capacity at 700 rpm is 917,113 kg/hour. The best average thickness is also at 700 rpm which is 5,9991 mm. The best percentage of damaged material is 600 rpm, which is the smallest with a value of 15,53%. The smallest amount of material left behind is 600 rpm, which is 7.2%. The lowest energy use in this variation is at 800 rpm, which is 0.346 mL, so the smallest cost in terms of fuel consumption is at 800 rpm, which is Rp. 3,460.